Food and nutrition policies in Africa: capacity challenges and training options - Babu, Suresh Chandra (African Journals Online, 2001)
This paper is an attempt to provide an overview of the challenges that face nutrition planners and policymakers in implementing and evaluating nutrition policies and program interventions [in sub-Sharan Africa.]--Abstract.